Experimental studies of the effectiveness of the influence of the technology of lining the steel parts on contact strength. - Марченко, Д.Д. (Problems of Tribology, 2017)
The results of investigations of the physical and mechanical properties of the surface layer and electron-graphical studies of the microstructure of the shafts are given in the article, after hardening by surface plastic deformation by rolling by rollers. A mechanism is described for the appearance of dislocation cells in the grain structure due to the dislocation density after rolling. The study of the technological process of surface hardening of steel parts by rolling with rollers, as well as certain design and technological parameters of the device for rolling over the indicators of the technological process of hardening of cathode blocks with the purpose of increasing their contact strength, which allows to optimize the technological process.The set of laboratory instruments for experimental studies of the physical and mechanical properties of complex shaped steel parts that work under a contact load, including a cable block, such as the degree of hardening of the working surface and the roughness of the rolled surface. The increase in the degree of cold work during roller rolling manifests itself in a greater density of dislocations and a decrease in the size of the cells in the substructure of ferrite grains, as well as in a denser network of dislocations in perlite ferritic plates. The conducted experimental researches have proved the adequacy of the results of physical and mathematical modeling of the processes that occur during the rolling of the working surface of the cable block with a wedge roller.Key words: contact strength, wear, diffusion, surface plastic deformation, wedge roller, rope block.